Clinical Application of Restrictive Brace Combined with Psychological Intervention after Replantation of Severed Fingers in Children. (30th June 2022) - Chen, Guangxian; Wang, Wei; Wang, Ping; Zhang, Ning; Xiu, Xiaolei; Zhao, Jianyong
Abstract : Objective . After replantation of severed fingers in infants, the utility model patent upper limb restrictive brace-assisted bed rest braking, combined with psychological intervention, can alleviate children's anxiety, so as to reduce the occurrence of vascular crisis. Methods . The study period was from April 2015 to July 2018. In this paper, 30 children with finger injuries in hand surgery in the CIS electronic medical record system of Cangzhou Integrated Traditional Chinese and Western Medicine Hospital were selected as the research objects. Replantation was performed in 30 infants with severed fingers. Among them, 15 cases were applied with the method of aircraft chest arm gypsum splint combined with sedative drug braking and the utility model patented product upper limb restrictive brace fixation-assisted bed rest braking, and the method of psychological intervention was applied at the same time. Results . Among the 15 fingers in the control group, 6 had vascular crisis and 1 in the experimental group. The incidence of vascular crisis in the experimental group was lower, and the difference between the two groups was statistically significant (P < 0.05 ). The patients were followed up for 9 18 months, with an average of 9.72 ± 1.07 months. In the control group, 15 cases of severed fingers survived, and there were 13 cases of replantation finger necrosis in 2 cases of intractable arterial crisis. In the experimental group, 14 cases of severed fingers survived in 15 cases and there was 1 case of replanted finger necrosis in intractable arterial crisis after operation. There was no significant difference in the survival rate between the two groups (P > 0.05 ). In addition, the replanted finger function was evaluated. In the control group, 9 cases were excellent, 4 cases were good, and 1 case was fair. In the experimental group, 14 cases were excellent, 1 case was good, and 0 case was fair. The functional evaluation of the experimental group was better than that of the control group, and the difference between the two groups was statistically significant (P < 0.05 ). Conclusion . For infants after replantation of severed fingers, the application of the utility model patented product upper limb restrictive brace can effectively make up for the insufficient fixation of aircraft chest arm gypsum splint, reduce the occurrence of vascular crisis, and assist children in bed. In addition, the application of psychological intervention can reduce children's postoperative crying and is conducive to children's postoperative recovery.